Lexical Innovation in Arabic Grammar Studies: The Development of a Thematic Dictionary for Kawākib ad-Durriyyah - Eliza Oktavia; Yasmadi Yasmadi; Rahmawati Rahmawati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The Kitab Kawākib ad-Durriyyah is a traditional Arabic grammar text commonly used in Islamic boarding schools (pesantren) for teaching nahwu. However, its exclusive use of classical Arabic, complex terminology, and absence of diacritical marks pose significant challenges for learners unfamiliar with Arabic. This study aims to develop a thematic dictionary as a supportive learning tool to facilitate understanding of Kawākib ad-Durriyyah. Employing a Research and Development (R&D) approach with the ADDIE model, the study involved stages of analysis, design, development, implementation, and evaluation. The findings revealed that learners’ needs reached 83.38% and teachers’ needs 83.33%, both categorized as “strongly agree,” indicating a high demand for such a tool. The thematic dictionary was developed through four stages—cover design, content structuring, expert validation, and product revision—and includes vocabulary items, word forms, roots (fi‘l māḍī and maṣdar), and their translations. Validation results showed high ratings from experts: 93.33% (design), 97.5% (content), and 95.55% (language), all in the “very good” category. Field testing produced positive responses from both students (89.15%) and teachers (86%). The study contributes to Arabic language pedagogy by providing an innovative lexical aid that bridges traditional grammar learning with modern instructional design principles.